Digital Transformation in Talent Management: A Systematic Literature Review on Msme Retention Strategies - Agus Kurniadi; Sudarmiatin Sudarmiatin; Agus Hermawan (International Forum of Researchers and Lecturers, 2025)
This study conducts a systematic literature review (SLR) and bibliometric analysis to map and synthesize research on digital transformation in talent management and its impact on employee retention in Micro, Small, and Medium Enterprises (MSMEs). Against the backdrop of high turnover rates and intense competition for talent, this research aims to identify the key interconnections between digital technologies, talent management practices, and retention outcomes within the MSME context. The methodology involved a comprehensive analysis of reputable databases using VOSviewer software for bibliometric mapping, focusing on co-authorship, co-occurrence, and citation networks. The findings reveal a robust, interconnected model centered on three core pillars: the adoption of digital technologies (e.g., AI, cloud-based HR systems), the implementation of strategic talent practices (notably digital employer branding and work flexibility), and the critical mediating role of employee psychological factors (job satisfaction and organizational commitment). The analysis demonstrates that successful retention in MSMEs is not merely a function of technological adoption but is achieved through a synergistic integration where technology enables effective talent management, which in turn fosters commitment and reduces turnover intention. This review contributes a comprehensive conceptual model that clarifies these dynamic relationships. The practical implication for MSME managers is the necessity of a holistic strategy that simultaneously develops digital infrastructure, refines talent management, and cultivates a supportive organizational culture to secure a sustainable competitive advantage through enhanced employee retention.